2014
DOI: 10.1590/s0102-86502014000600006
|View full text |Cite
|
Sign up to set email alerts
|

A cadaveric study to determine the minimum volume of methylene blue to completely color the nerves of brachial plexus in cats. An update in forelimb and shoulder surgeries

Abstract: PURPOSE:To determine the minimum volume of methylene blue (MB) to completely color the brachial plexus (BP) nerves, simulating an effective anesthetic block in cats. METHODS:Fifteen adult male cat cadavers were injected through subscapular approach with volumes of 2, 3, 4, 5 and 6 ml in both forelimbs, for a total of 30 brachial plexus blocks (BPB). After infusions, the specimens were carefully dissected preserving each nervous branch. The measurement of the effective area was indicated by the impregnation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 20 publications
3
16
0
Order By: Relevance
“…In this study, in line with the findings reported for cats (McClure et al, ), it was determined that the radial nerve was formed by the ventral branches of the 7th and 8th cervical nerves. In line with the findings asserted in the literature (Aubert et al, ; Mencalha et al, ), this study observed that after giving off a muscle branch for the medial head of the triceps brachii muscle, the radial nerve was divided into the superficial branch and the deep branch.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this study, in line with the findings reported for cats (McClure et al, ), it was determined that the radial nerve was formed by the ventral branches of the 7th and 8th cervical nerves. In line with the findings asserted in the literature (Aubert et al, ; Mencalha et al, ), this study observed that after giving off a muscle branch for the medial head of the triceps brachii muscle, the radial nerve was divided into the superficial branch and the deep branch.…”
Section: Discussionsupporting
confidence: 91%
“…It was reported that the radial nerve was formed by the ventral branches of the 7th and 8th cervical (McClure et al, ) or the 7th and 8th cervical and the 1st thoracic nerves (Anson et al, ; König & Liebich, ; Mencalha et al, ). In this study, in line with the findings reported for cats (McClure et al, ), it was determined that the radial nerve was formed by the ventral branches of the 7th and 8th cervical nerves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study of anatomical landmarks, morphology and morphometric are important to optimize the results of surgical and anesthetic interventions 2,3 . Until the last century, locoregional blocks were exclusively performed through anatomical references, and consequently had high rates of failure and injury.…”
Section: Introductionmentioning
confidence: 99%